Literature Study: Analysis the Role of Teachers as Models in Strengthening Character in Primary School Learners - Jumatullailah, Siti Nurfebri; Arifin Maksum; Nina Nurhasanah (At-Taqaddum, 2024)
The development of character in primary school learners is a fundamental aspect of education that lays the groundwork for future moral and ethical behavior.  Teachers, as the primary pillars in the learning process, hold a critical responsibility in shaping the character of primary school learners.  The complexity of the teacher's role as a model in character education necessitates a comprehensive understanding and evaluation of their influence.  This study aims to provide a new contribution by offering a more general and conceptual exploration of the role of teachers in strengthening character among primary school learners. The focus of this approach is to analyze the Role of Teachers according to UU No. 14 Tahun 2005 concerning Teachers and Lecturers, the integration of character values in learning, teacher practices, and the impact of teacher behavior on students.  This study employs qualitative methods through relevant literature review. Using a descriptive-holistic approach, the research aims to provide a comprehensive understanding of the topic.  The results of the study are in the form of an analysis of the role of teachers as role models in strengthening positive character in elementary school students in accordance with Law of the Republic of Indonesia Number 14 of 2005 concerning Teachers and Lecturers. How the role of teachers can be a model in strengthening positive character in elementary school students. The efforts that primary school teachers make in their roles reinforce positive character in students, both inside and outside the classroom.